2017
DOI: 10.1016/j.jpainsymman.2017.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Communication Challenges of Oncologists and Intensivists Caring for Pediatric Oncology Patients: A Qualitative Study

Abstract: We identified barriers to communication with families both within and between teams and for individual physicians. Formal communication training and processes that standardize communication to ensure completeness and role delineation between clinical teams may improve oncologists' and intensivists' ability to initiate GCDs, thereby fulfilling their ethical obligations of decision support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 19 publications
3
51
0
7
Order By: Relevance
“…Deliberations within the mixed group attributed higher information quality ratings from those reported in the palliative care-and oncology-only groups at Hospital 2 but lower at Hospital between palliative care and oncology teams at the diagnostic stage in which the LDT will be implemented. This nding corroborates what has been found in the patient decision-making and communication literature speci c to the care of critically ill children with cancer (24).…”
Section: Discussionsupporting
confidence: 89%
“…Deliberations within the mixed group attributed higher information quality ratings from those reported in the palliative care-and oncology-only groups at Hospital 2 but lower at Hospital between palliative care and oncology teams at the diagnostic stage in which the LDT will be implemented. This nding corroborates what has been found in the patient decision-making and communication literature speci c to the care of critically ill children with cancer (24).…”
Section: Discussionsupporting
confidence: 89%
“…43 A single event, such as receiving bad news in an insensitive way (via vocal or body behavior), or the feeling of being dismissed can cause parents profound distress 31 and increase anxiety, distrust, and dissatisfaction with care. 44 The presence of a nurse during family meetings can increase parents' understanding of key discussion points. 45 Along with team members such as social workers, child-life therapists, psychologists, and chaplains, nurses can serve as a voice for families and help inform physicians about parents' wishes.…”
Section: Open and Honest Information Sharing When Given The Green Lightmentioning
confidence: 99%
“…4,5 Fellows and Attendings in fields with high exposure to EOL situations including the pediatric intensive care unit and Hematology/Oncology report lack of education and training as a barrier to having goals of care and EOL conversations. 18,19 Emerging research has also identified that pediatric trainees caring for a patient who dies frequently exhibit diagnostic criteria of acute stress reaction (ASR) or posttraumatic stress disorder (PTSD) with a small percentage actually meeting criteria for these diagnoses. 7 Discrepancies in the recognition of the need for palliative care education among residents and their program directors has improved, 6 with a recent national survey of pediatric program directors concluding that 81% of all respondents and 96% of general pediatrics program directors felt palliative care education would be beneficial.…”
Section: Introductionmentioning
confidence: 99%